EFEKTIVITAS AROMATERAPI LAVENDER TERHADAP PENURUNAN STRES PADA IBU HAMIL DI RSU PKU MUHAMMADIYAH GUBUG - yeni kisworo; Indah Puspitasari; Indah Risnawati (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2026)
Pregnancy is a physiological process accompanied by physical, psychological, and social changes that can trigger stress. Stress that is not properly managed can have a negative impact on maternal and fetal health, such as an increased risk of premature birth, low birth weight, and child developmental disorders. One of the non-pharmacological therapies that can be used to reduce stress is lavender aromatherapy, which has a relaxing effect through the content of linalool and linalyl acetate. Aim of the research was to determine the effectiveness of lavender aromatherapy on reducing stress levels in pregnant women at PKU Muhammadiyah Gubug Hospital. This study used a quasi-experimental design with a pre and post test design without a control group. The research population was all pregnant women who visited PKU Muhammadiyah Gubug Hospital in May-June 2025 with a sample of 39 respondents selected using purposive sampling. The intervention was carried out by giving lavender aromatherapy inhalation 2–3 drops on a cotton swab for 15–30 minutes every day for 7 days. Stress levels were measured using the Perceived Stress Scale (PSS-10) questionnaire. The data were analyzed using the Wilcoxon test. The results of statistical analysis of the wilcoxon test obtained p value = 0.000. It can be concluded that there is an Effectiveness of Lavender Aromatherapy in Reducing Stress in Pregnant Women at PKU Muhammadiyah Gubug Hospital. There was an Effectiveness of Lavender Aromatherapy in Reducing Stress in Pregnant Women at PKU Muhammadiyah Gubug Hospital.